2018
DOI: 10.1074/jbc.ra118.004516
|View full text |Cite
|
Sign up to set email alerts
|

Probing the contribution of individual polypeptide GalNAc-transferase isoforms to the O-glycoproteome by inducible expression in isogenic cell lines

Abstract: The GalNAc-type O-glycoproteome is orchestrated by a large family of polypeptide GalNAc-transferase isoenzymes (GalNAc-Ts) with partially overlapping contributions to the O-glycoproteome besides distinct nonredundant functions. Increasing evidence indicates that individual GalNAc-Ts coregulate and fine-tune specific protein functions in health and disease, and deficiencies in individual GALNT genes underlie congenital diseases with distinct phenotypes. Studies of Gal-NAc-T specificities have mainly been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 70 publications
(114 reference statements)
1
37
0
Order By: Relevance
“…Studying O-GalNAc glycoproteins by MS-based glycoproteomics is complicated by glycan heterogeneity, the lack of O-glycosylation consensus sequences, and selective enrichment tools. Further complexity is added by the interplay of 20 GalNAc transferase (GalNAc-T1…T20) isoenzymes that mediate the first O-GalNAc biosynthesis step (22, 23). In a “bump-and-hole” (BH) approach, we have recently engineered GalNAc-Ts to carry a double mutation to preferentially accept UDP-GalNAc analogs with bulky chemical, editable tags (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Studying O-GalNAc glycoproteins by MS-based glycoproteomics is complicated by glycan heterogeneity, the lack of O-glycosylation consensus sequences, and selective enrichment tools. Further complexity is added by the interplay of 20 GalNAc transferase (GalNAc-T1…T20) isoenzymes that mediate the first O-GalNAc biosynthesis step (22, 23). In a “bump-and-hole” (BH) approach, we have recently engineered GalNAc-Ts to carry a double mutation to preferentially accept UDP-GalNAc analogs with bulky chemical, editable tags (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…The non-synonymous serine-to-leucine SNP changes a conserved residue within the Ricin B lectin domain of GALNT11 and would be predicted to impede O-linked glycosylation. GALTN11 has been shown to uniquely glycosylate at least 313 glycoproteins in HEK cells 33 . Using the Jaccard similarity tool in the GeneWeaver 34 system for integrative functional genomics, we determined that of the 313 human glycopeptides, 287 mouse orthologs are expressed in the mouse pre-Bötzinger complex 32 (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the functional sufficiency of Galnt11 as a candidate gene the literature was searched to identify genome-wide studies characterizing glycosylation targets of GALTN11, one study was identified 33 and these genes were added to the GeneWeaver Database (GS356053). Using the Jaccard similarity tool, we overlapped the glycosylation targets with the genes expressed in the mouse pre-Bötzinger complex.…”
Section: Methodsmentioning
confidence: 99%
“…Knock-outs of single GalNAcTs in the SimpleCell background have been profiled by glycosproteomics (18,21). Similarly, glycopeptides from non-SimpleCells with titratable GalNAcT knock-in have been enzymatically simplified to allow for enrichment and MS (22).…”
mentioning
confidence: 99%
“…These studies have revealed comprehensive glycoproteomics datasets, but suffer from loss of 20 glycan elaboration and laborious genome engineering required for targeted knock-in. Further, the activity of GalNAcT isoenzymes is both redundant and competitive, such that compensation and/or 4 shift of glycosylation sites occurs upon knock-out (21,22). A gain-of-function strategy to visualize the products of a particular GT on the living cell is currently elusive.…”
mentioning
confidence: 99%